Isu dan Cabaran dalam Pemahaman Aqidah di Kedah Malaysia (Perbandingan Antara Generasi Tua dan Muda) - Salman Abdul Muthalib; Noval Liata; Syukran Abu Bakar; Muhammad Wildan Nafis; Muhammad Ariff Muzakkir Bin Zakaria; Miftahul Khair K; Nisa Ul Awla; Muhammad Hafifi; Afkar Zharief; Furqan Syahputra Muharli; Amelia Anggraena; Kaulama Puger Melala; Nik Ahmad Annasaei Bin Nikmat; Tuan Muhammad Akma Asyraaf Bin Tuan Mohd Nasir; Rijal Fandika (Jurnal Riset dan Pengabdian Masyarakat, 2025)
Issues and challenges regarding understanding Aqidah are interesting things to research, considering the long history of the development of Islam in the State of Kedah, which strictly adheres to the Aqidah of Ahli Sunnah Wal Jama'ah. The Sultanate and Islamic clerics of Kedah strive that the Aqidah Ahli Sunnah Wal Jama'ah education delivered by Imam Abu Hasan al-Asy'ari and Imam Abu Mansur al-Maturidi must be accepted by all Kedah Muslims. This study discusses the issues and challenges in understanding the Aqidah of Muslims in the State of Kedah, Malaysia, with a focus on the comparison between the older and younger generations. Major changes in social frameworks, technology and global cultural influences have had a significant impact on the thinking and understanding of Aqidah, the older generation tends to be more attached to traditions, Islamic boarding school teachings and recitations at each mosque. Meanwhile, the younger generation who are exposed to various forms of information media tend to find it difficult to learn in a structured and traditional manner. This study uses a qualitative approach through interviews and document findings and pays attention to empirical factors to identify differences in understanding patterns between the two generations. And how to turn the challenge of these differences into an opportunity to increase understanding of Aqidah in both the older and younger generations. This article emphasizes the importance of an approach to preaching and Aqidah education that is inclusive, dynamic and keeps up with current developments so that understanding of Aqidah between generations can be strengthened.